Liver transplantation for critically ill cirrhotic patients: Stratifying utility based on pretransplant factors. Issue 9 (15th April 2020) - Artzner, Thierry; Michard, Baptiste; Weiss, Emmanuel; Barbier, Louise; Noorah, Zair; Merle, Jean‐Claude; Paugam‐Burtz, Catherine; Francoz, Claire; Durand, François; Soubrane, Olivier; Pirani, Tasneem; Theocharidou, Eleni; et al.
Abstract : The aim of this study was to produce a prognostic model to help predict posttransplant survival in patients transplanted with grade‐3 acute‐on‐chronic liver failure (ACLF‐3). Patients with ACLF‐3 who underwent liver transplantation (LT) between 2007 and 2017 in 5 transplant centers were included (n = 152). Predictors of 1‐year mortality were retrospectively screened and tested on a single center training cohort and subsequently tested on an independent multicenter cohort composed of the 4 other centers. Four independent pretransplant risk factors were associated with 1‐year mortality after transplantation in the training cohort: age ≥53 years ( P  = .044), pre‐LT arterial lactate level ≥4 mml/L ( P  = .013), mechanical ventilation with PaO2 /FiO2  ≤ 200 mm Hg ( P  = .026), and pre‐LT leukocyte count ≤10 G/L ( P  = .004). A simplified version of the model was derived by assigning 1 point to each risk factor: the transplantation for Aclf‐3 model (TAM) score. A cut‐off at 2 points distinguished a high‐risk group (score >2) from a low‐risk group (score ≤2) with 1‐year survival of 8.3% vs 83.9% respectively ( P  < .001). This model was subsequently validated in the independent multicenter cohort. The TAM score can help stratify posttransplant survival and identify an optimal transplantation window for patients with ACLF‐3. Abstract : A score comprised of four objective pretransplant risk factors stratifies posttransplant survival among decompensated patients with cirrhosis with multiple organ failure and may guide clinician decision‐making regarding liver transplant suitability. See the editorial from Sundaram on page 2297 .